2019
DOI: 10.5530/ijmedph.2019.4.24
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Effects of Stunting on Human Capital: Where Does the Compass Point?

Abstract: Development of any nation hinges on its human capital. Human capital formation starts from early stages of childhood. Early childhood nutrition is one of the determinants of improved health and development. The purpose of this paper is to investigate the role of nutrition in impacting cognitive development, education attainment and skill development, which are the determinants of human capital. This is an attempt to analyse the intrinsic relationship between stunting and its intergenerational impact on human c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
10
0
2
Order By: Relevance
“…Stunting is a marker of chronic malnutrition that affects 144 million children and causes significant disease burden worldwide (1,2) . Stunting is an important determinant of human capital and is a predictor of economic productivity (3)(4)(5) . It is linked to poorer cognitive and educational outcomes (6,7) , lower wages (8,9) , and poorer health in adult life (3,10) .…”
mentioning
confidence: 99%
“…Stunting is a marker of chronic malnutrition that affects 144 million children and causes significant disease burden worldwide (1,2) . Stunting is an important determinant of human capital and is a predictor of economic productivity (3)(4)(5) . It is linked to poorer cognitive and educational outcomes (6,7) , lower wages (8,9) , and poorer health in adult life (3,10) .…”
mentioning
confidence: 99%
“…It is clear that habits of pica, food aversions, and cravings predispose women to low food intakes and ultimately malnutrition in developing countries. Thus, pregnant women to avoid nutritious foods such as animal-source foods, cereals, and legumes, aggravating the risk of micronutrient deficiencies ( 8 , 57 ). Hormonal changes during pregnancy and culturally specific food taboos are the main drivers of consumption of non-nutritious foods and non-food items ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, evidence from Ethiopia showed that women who received dietary counseling had 7–8 times better dietary practices (AOR = 7.2; 95% CI: 4.49, 11.49). These urges for enhanced comprehensive and targeted dietary counseling for pregnant women should be strengthened for a better maternal and fetal nutrition in Ethiopia ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant proportion (78.2%) of children ate more than three times a day, while 96.4% of children routinely defined everyday meals and advised that parents encourage their children's healthier eating habits. Chakravarty, Tatwadi, and Ravi (2019) examined the intrinsic relation between stunting and its intergenerational impact on human capital from 1986 to 2017 in South Asian and Sub-Saharan countries. The study found that the formation of human capital starts in the early stages of childhood.…”
Section: Review Of Literaturementioning
confidence: 99%